Influence Of Principles And Independence Accountability Preferences On Muzakki Pay Zakat In Amil Institutions Zakat Izi PKPUKota Bukittinggi - septria susanti; Aidil Alfin (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
This study aims to analyze whether the accountability and independency principles affect the preferences of muzakki to pay zakat to zakat management institutions. This study uses saturated samples by involving all members of the population as many as 30 permanent muzakki people who routinely pay their zakat to the PKPU Bukittinggi IZI Amil Zakat Institution. This study reveals that the accountability and independency principle has a positive and significant effect on muzakki's preference to pay zakat to zakat management institutions. These findings offer empirical evidence that it is important to implement accountability and independency principles in a zakat management organization to create muzakki preferences. With the existence of a clear system of accountability and reporting and the application of sound organizational principles, muzakki still chooses to distribute their zakat to the zakat management institution itself. Furthermore, this research recommends the strategy to increase muzakki trust in amil zakat institutions.